Effect of high-starch or high-fibre diets on the energy metabolism and physical performance of horses during an 8-week training period - Martin, Agathe; Lepers, Romuald; Vasseur, Maximilien; Julliand, Samy (Frontiers in Physiology, 2023)
Large amounts of high-starch concentrates are traditionally fed to horses in training. However, this has been associated with digestive or muscle diseases, and behavioural modifications. In parallel, it has been demonstrated that horses fed high-fibre, low-starch diets achieve the same performance over an exercise test as the ones fed high-starch diets. However, whether the same performance level can be maintained over a longer training cycle is still being determined. This study aimed to compare the evolution in physical performance and cardiorespiratory responses of two groups of French Trotters fed either a control high-starch (15.0 g dry matter hay/kg body mass/day + 6.6 g dry matter oats/kg body mass/day) or a high-fibre diet (75% of oats replaced by dehydrated alfalfa) over an eight-week training period. The horses that entered the trial were untrained for ≥4 months and previously fed hay only. Track training with speed monitoring included interval training (IT) sessions and 2400-m performance tests from week 1 to week 8 (W8). Before (week 0, W0) and after (week 9, W9) the training period, horses performed an incremental continuous exercise test (ICET) during which cardiorespiratory parameters were measured. Both groups progressed to the same extent regarding physical performance measured during IT sessions (acceleration: 0.16 m.s-2 at W0, 0.40 m.s-2 at W8; P<0.0001), 2400-m performance test (average speed: 8.88 m.s-1 at W0, 10.55 m.s-1 at W8; P<0.0001), and ICET (speed during fastest stage: 9.57 m.s-1 at W0, 10.53 m.s-1 at W9; P=0.030). Although oxygen consumption increased with training (P=0.071), it was not influenced by the diet. On contrary, carbon dioxide production increased in group high-starch group only (high-starch group: 84.0 vs high-fibre group: 77.7 ml.kg-1.min-1 at W9; P=0.031). The results illustrate that horses in both groups progressed similarly but did not use the same metabolic pathways during exercise. This hypothesis is supported by carbohydrate oxidation, which tended to increase in high-starch group at W9 but decreased in high-fibre group (P=0.061). In conclusion, the substitution of high-starch by high-fibre diets enabled similar performance over an 8-week training period and altered energy metabolism in a way that could be beneficial during high-intensity exercise.